Serial MRI findings of acute flaccid myelitis during an outbreak of enterovirus D68 infection in Japan - Okumura, Akihisa; Mori, Harushi; Fee Chong, Pin; Kira, Ryutaro; Torisu, Hiroyuki; Yasumoto, Sawa; Shimizu, Hiroyuki; Fujimoto, Tsuguto; Tanaka-Taya, Keiko (Brain & development (Tokyo. 1979), 2019)
To clarify the neuroimaging findings of children with acute flaccid myelitis during an outbreak of EV-D68 infection. We performed a detailed review of the spinal and cranial MRI results of 54 children with acute flaccid myelitis. We focused on the range of longitudinal lesions, the localization and appearance of lesions within a horizontal section, Gadolinium-enhancement, and changes over time. All children had longitudinal spinal lesions involving central gray matter. Twenty-six children had lesions spanning the entire spine. Six of them had weakness in all limbs, whereas seven had weakness of only one limb. Thirty-eight children had lesions in both gray and white matter and limb weakness tended to be more severe in these children. During the acute period, spinal lesions showed bilateral ill-defined widespread T2 hyperintensity. During the subacute period, lesions were well defined and confined to the anterior horn. The distribution of limb weakness was correlated with the appearance of lesions during the subacute period. Gadolinium enhancement was performed in 37 children, and enhancement was seen in the cauda equina in 29 children. Enhancement was infrequent within 2 days after onset but was seen in almost all children thereafter. Twenty-two children had brainstem lesions continuous with spinal lesions. Extensive longitudinal spinal lesions were characteristic in children with acute flaccid myelitis. Lesions were usually bilateral and widespread during the acute period, whereas localization to the anterior horn could become obvious. Although enhancement of the cauda equina was often observed, its appearance was sometimes delayed.